G455 Antenatal advance care planning: 3 years experience from a single centre. (7th April 2014) - Holt, S; Lim, J; Jones, C; Bricker, L; Turner, M; Agarwal, U; Subhedar, N; Brook, L
Abstract : Background: Advance care planning can improve outcomes including achieving preferences for setting of end of life care and appropriate use of life prolonging interventions. We have extended advance care planning to the parents of fetuses antenatally diagnosed with conditions that may require palliative care. Aims: To identify precipitating factors, timing and outcomes of antenatal advance care planning and compare with circumstances of end of life. Methods: Retrospective review of antenatal palliative care referrals over a 3-year period. Results: Fourteen mothers were offered antenatal advance care planning. Eleven foetuses had congenital heart disease; two Edwards syndrome; other diagnoses foetal alcohol syndrome, Potter syndrome, diaphragmatic hernia, duodenal atresia, cerebral ventriculomegaly with intraventricular haemorrhage and thin cerebral cortex. Two foetuses had healthy twins. Eleven families met with the team comprising foetal medicine, neonatology, paediatric palliative care and relevant paediatric specialties. Discussions included place and mode of delivery, care immediately after birth and setting of choice for end of life care. Three families opted to continue with attempts at life prolonging surgery. Input from the palliative care team influenced choices in place of delivery, mode of delivery and setting for care after birth. Thirteen of these babies have since been born; nine have died; two on the labour ward; one on the neonatal intensive care unit at 3 days of life; four in a children's hospice between 5 and 45 days of age; one baby at home at 9 days of age; one at 567 days from intercurrent illness on paediatric intensive care following successful palliative cardiac surgery. Two babies are still alive at 428 and 19 days. No outcome data was available for two. Conclusions: Antenatal advance care planning is an acceptable intervention that may alter preferences for place of delivery, mode of delivery and setting for care after birth. It is important to recognise that outcomes may be different to expectations and perinatal care plans need to reflect this.